Entrepreneurship Education Context Islamic Perspective: Concepts, Characteristics, Processes, and Their Values - Noni Yuanda (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Looking at Indonesia's entrepreneurship index which is still low. Entrepreneurship education needs to be considered to seize sharia-based industry business opportunities. For this reason, it is necessary to develop sharia-compliant entrepreneurial human resources. This article aims to analyze the basic concepts, characteristics, processes, and values of entrepreneurship in an Islamic perspective that can be applied in Islamic entrepreneurship material so that it can be used as teaching material in schools and universities. The type of research used is qualitative with a conceptual library research design that makes library materials the main data source, namely examining several sources of books, journals and websites related to the research theme. The result of the writing that is expected later is that the concept and value of Islamic entrepreneurship must remain based on the teachings of the Al-Quran and Al-Hadith as a form of obedience and a sense of responsibility to Allah SWT. The concept of entrepreneurship of the Prophet Muhammad that Muslims need to own and apply, namely fathanah, amanah, shiddiq, and tabligh.